2019
DOI: 10.1017/dmp.2019.91
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Preparedness Plans for Chemical Incidents and Threats: A Systematic Review

Abstract: In a wide range of events, people may be acutely exposured to chemical substances. Particular hospital preparedness plans and vital resources are essential for appropriate health-care measures. The present study aimed to conduct a systematic review to summarize and evaluate the existing evidence on hospital preparedness plans or protocols against chemical incidents and threats. In this aim, through May 15, 2018, 5 electronic databases were searched in MEDLINE (PubMed, Scopus, Web of Science, Cochrane Library, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…L'évaluation du risque pour la santé humaine est un processus qui comprend trois composantes successives, à savoir : l'évaluation, la gestion et la communication. Par ailleurs, la gestion d'un incident chimique majeur peut être interprétée à plusieurs niveaux : institutionnel, scientifique, opérationnel et formatif (1). L'information doit être disponible et accessible (2).…”
Section: Contexte Et Problématiqueunclassified
See 1 more Smart Citation
“…L'évaluation du risque pour la santé humaine est un processus qui comprend trois composantes successives, à savoir : l'évaluation, la gestion et la communication. Par ailleurs, la gestion d'un incident chimique majeur peut être interprétée à plusieurs niveaux : institutionnel, scientifique, opérationnel et formatif (1). L'information doit être disponible et accessible (2).…”
Section: Contexte Et Problématiqueunclassified
“…Le présent article est axé sur l'évaluation du risque définie comme un ensemble d'analyses scientifiques dont les résultats sont des expressions quantitatives ou qualitatives de la vraisemblance de dommages causés par l'exposition à un produit chimique (11). Sur le plan opérationnel, une équipe spécialisée réunissant les départements médical, infirmier et paramédical, responsable en cas de situations d'incidents chimiques majeurs, devrait être formée à l'évaluation de l'exposition et aux risques associés (1,12). Cette équipe doit maîtriser les étapes d'évaluation du risque afin de se prémunir contre tout risque de contamination.…”
Section: Contexte Et Problématiqueunclassified
“…Most countries have equipped hospitals against chemical incidents, but some aspects remain challenging, such as databases, response team members, communication, etc. [27]. Rebmann et al [28] suggested that hospitals should use appropriate planning tools to support the development of intervention plans.…”
Section: Indicators For Healthcare Service Designmentioning
confidence: 99%
“…[23][24][25][26][27] Similarly, the journal has reported on findings and discussions surrounding hazardous chemical materials, including but not limited to reports on preparedness, 28,29 training exercises, 30 case studies, 31,32 and review articles. 33,34 For these reasons, the meeting organizers began working with the journal at the very beginning of the process, leading to the publication of this meeting report and the special issue in which it resides.…”
Section: About the Journal Selection For A Special Issue (J James)mentioning
confidence: 99%
“…A clinical trial of high-dose vitamin D3 against Valchlor ™ , an FDA-approved topical NM, in healthy volunteers 34 involved multiple observations, and biopsies, as well as blood draws. These results showed that most of the pathways involved in the injury and treatment mitigation were related to inflammation, including leukocyte, lymphocyte, and chemokine activation; patients also experience a decrease in erythema, swelling, and pain.…”
Section: Cutaneous Radiation Injury (Cri) (C Iddins)mentioning
confidence: 99%